The Philippines in 2012: "Easygoing, do-nothing" president delivers - De Castro, Renato Cruz (Animo Repository, 2013)
Two years into his presidency, Benigno Simeon Aquino III has been described as an absentee, do-nothing president by his detractors. A review of the key economic and political developments in 2012, however, reveals that his administration has chalked up a list of accomplishments. Thus, despite his easygoing and laid-back leadership style, the president has shown he can deliver. © 2013 by the Regents of the University of California. All rights reserved.